A dexamethasone, melphalan, actinomycin‐D and cytarabine chemotherapy protocol as a rescue treatment for feline lymphoma. (16th October 2017) - Elliott, J.; Finotello, R.
Abstract : Nineteen cats with relapsed high‐grade/large‐cell lymphoma were treated with dexamethasone, melphalan, actinomycin‐D and cytarabine (DMAC). All cats had received Cyclophosphamide, Vincristine, Prednisolone (COP) as first‐line chemotherapy and most cats had received at least 2 prior rescue agents with 14 of 19 having received both epirubicin and lomustine. Five cats (26%) exhibited a response (defined as an improvement or resolution of tumour‐associated clinical signs/tumour volume, or complete/partial response) to chemotherapy though no patients received more than 2 cycles of DMAC. Most cats tolerated the protocol well though 3 patients exhibited Veterinary Cooperative Oncology Group (VCOG) grade 4 neutropenia and 1 patient exhibited grade 4 thrombocytopenia. The median progression‐free survival and overall survival from starting DMAC were 14 and 17 days respectively. There is still an unmet need for successful rescue chemotherapy protocol for cats with relapsed lymphoma. [Correction added on 02 November 2017, after first online publication: The expansion for the term DMAC was previously incorrect and has been corrected in this current version.]